Taqyīm Manāhij al-Tarbiyyah al-Islāmiyyah fī Madāris Myanmar al-Islāmiyyah: ‘Arḍ wa Naqd: Evaluation of Islamic Education Curriculum in Myanmar Islamic Schools: A Review and Criticism - Muhammed Sayed, Anowar Sadek; Ismail, Halim (Jurnal Usuluddin, 2021)
This article aims to evaluate Islamic educational curricula in Islamic schools of Myanmar. The article includes an introduction, a brief about Myanmar, the advent of Islam to it, the emergence of Islamic educational institutions, the educational system and its instructional methods, the stages of study, and the curricula. It has employed the descriptive method to present the history of the arrival of Islam in Myanmar and the educational system and the critical method to point out the aspects of the shortcomings of the system. Among the findings are that: these educational curricula in Myanmar schools do not generate the expected results in nurturing the young generation and spreading Islamic sciences and cultures among a Muslim minority, it has not witnessed any development or reform since its inception to this day, the schools need professionally trained teachers to teach this type of curricula, it needs to add some more important subjects to be comprehensive their traditional teaching methods and means should be developed and additional extracurricular activities should be enhanced to help develop students’ skills in order to qualify them to be cadres in the arena of change in the rapidly changing time. As this system does not meet the needs and requirements of the time it requires a professional review in all of its aspects.